Islamic Finance, Small and Medium Enterprises and Job Creation in Turkey: An Empirical Evidence (2009-2017) - Benbekhti, Seyf Eddine; Boulila, Hadjer; Bouteldja, Abdelnacer (International Journal of Islamic Economics and Finance (IJIEF), 2021)
The aim of this paper is to investigate if Islamic finance can solve the funding problem of SMEs and facilitate access to finance for SMEs, and how can these last participate in job creation in Turkey in order to face the problem of unemployment. The paper adopts a Vector Autoregressive model (VAR) based on monthly data (2009-2017). The results revealed that Islamic finance is a golden opportunity and a sufficient alternative financial source for SMEs. In addition, as SMEs can reduce unemployment by contributing to the labor market. This study contributes to the existing literature by presenting a promising financing tool to the prospective borrowers of SMEs (farmers, underserved groups, and small entrepreneurs) which is Islamic financing. This alternative can be an effective tool for both muslim and non-muslim countries in regard that conventional finance is more expensive and SMEs are unable to pay high interest rates. It would also help in establishing low unemployment levels.  This paper suggested that Islamic banks and Islamic financial institutions should converge more on the SMEs by providing funding to SMEs which would lead to boosting production and economic development.